Analysis of Higher Order Thinking Skills (HOTS) Content on Students’ Textbook of Natural and Social Sciences Subject for grade V Elementary School - Nurhayati Nurhayati; Tariza Fairuz (PT ARRUS Intelektual Indonesia, 2023)
One of the learning outcomes in the merdeka curriculum is that students have higher order thinking skills (HOTS) according to their respective phases, including phase C (for grades V and VI Elementary School). To achieve learning outcomes, it is necessary to have the role of textbooks as learning resources and media. This study aims to analyze the content of higher order thinking skills in the students’ textbooks of Natural and Social Sciences for grade V. This type of research is a descriptive quantitative study. Research data was collected through literature and documentation. The instrument used in this study is a checklist. The results of the research showed that the students' textbooks of Natural and Social Sciences for grade V is contained higher order thinking skills content in context and questions component.